PENGARUH BELANJA MODAL, BELANJA BARANG DAN JASA TERHADAP SISA LEBIH PEMBIAYAAN ANGGARAN (SILPA) KABUPATEN/KOTA di SULAWESI TENGAH - Iswahyudin, Iswahyudin (Katalogis, 2016)
The objectives of this study are :1) to find out the development of capital expenditure, good and service expenditure on budget surplus in districts/cities in Central Sulawesi; 2) to find out and analize simultaneous influence of capital expenditure, good and service expenditures on budget surplusÂ in districts/cities in Central Sulawesi; 3) to find out and analyze partial influence of capital expenditure on budget surplus in districts /cities in Central Sulawesi ; 4) to find out and analyze partial influence of good and service expenditures on budget surplus in districts/cities in Central Sulawesi. Population of this study consists of 13 districts/cities in Central Sulawesi and 11 districts/cities are selected as sample based on purposive sampling method. The research method used is verivication by means of multiple linear regressions analysis. The results of the test show that 50,40% of budget surplus is influenced by capital expenditure and good and service expenditure : while 49,6% is influenced by other factors, Multiple linear regression tests indicate that capital expenditure, good and service expenditures simultaneously and partially have significant influence on budget surplus in districts/cities in Central Sulawesi.